Understanding exposure texts: how much are images or drawings worth? - A.F. Pires; M. Amaral; P. Salvador; G. Bidarra; P. Vaz Rebelo (INFAD, 2019)
The main objective of the study was to analyze the influence of text characteristics, namely the integration of images and schemas, in interest and understanding perceived by students. Three types of different expository texts (simple expository text, expository text with schema and expository text with image) were elaborated. Participants were 69 students of classes of the 2nd cycle of basic education and were asked to read the text and answer to a survey that included questions about their interest and comprehension. The results showed that the expository text with image is what obtains higher levels of interest and understanding.